Ceftazidime/avibactam as a possible treatment option for carbapenem-resistant Enterobacterales infections - Ana Kaftandzieva; Gordana Mirchevska (Makedonsko Farmacevtski Bilten)
Carbapenem resistance (CR) in Enterobacterales is frequently determined by the production of enzymes, so called carbapenemases, (KPC, NDM, OXA-48 etc) or by porin deficiencies, combined with ESBLs. Several new agents with activity against certain carbapenemresistant pathogens have been approved for clinical use, such as ceftazidime-avibactam (CAZ-AVI). The aim of this study is to detect the resistance of Enterobacterales to the new combination CAZ-AVI which were recently approved for the treatment of infections due to CRE. In all 65 isolates the mechanisms of carbapenem resistance, i.e. the types of carbapenemases they produce, have been clearly defined by applying phenotypic and genotypic methods. New Vitek 2 susceptibility card (N-439) was used for determinаtion of susceptibility to antimicrobial agents including CAZ/AVI. Most of the isolates produced NDM, followed by OXA-48 carbapenemases. The highest percentage of NDM-producing isolates showed susceptibility to colistin (74%), while all OXA-48-producers (100%) showed susceptibility to CAZ/AVI. Many studies show that for bacteria with KPC, preferred treatment is the combination of βL-βLICs (Ceftazidime-avibactam, Meropenem-vaborbactam, and Imipenem-relebactam). For CRE producing metalo-beta-lactamases (NDM), preferred treatment is ceftazidime/avibactam in combination with aztreonam, and for those CRE which produce OXA-48, preferred treatment is ceftazidime/avibactam. Newly approved βL-βLICs are expected to offer many advantages, such as favorable safety profile and high activity against multi drug resistance gram-negative bacteria.